Current‐induced control of the electron–nuclear spin system in semiconductors on a micrometer scale. Issue 9 (20th May 2014) - Chen, Yuansen; Kim, Jungtaek; Puls, Joachim; Henneberger, Fritz; Bacher, Gerd; König, Jürgen; Oestreich, Michael
<x xml:space="preserve">Abstract</x> Microcoils, lithographically defined on top of a semiconductor are utilized for generating local on‐chip magnetic fields. Due to the low coil impedance, switching times on a sub‐nanosecond time scale are achieved allowing an ultrafast electrical manipulation and optical read‐out of the electron‐nuclear spin system. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>